Management of Leukemia and Partial Atrioventricular Septal Defect during Pregnancy - Li, Zhi; Sun, Haoliang; Li, Jinghang; Zhu, Yu (The Thoracic and Cardiovascular Surgeon Reports, 2021)
Background Pregnancy-associated acute myeloid leukemia (PA-AML) is rare. Cardiac surgery in the context of AML poses challenges that are seldom encountered.Case Description The subject is a 31-year-old woman at 38 weeks' gestational age diagnosed with AML and partial atrioventricular septal defect. After multidisciplinary consulting, an urgent cesarean section was performed, then chemotherapy was initiated, followed by minimally invasive cardiac surgery with an uneventful recovery.Conclusion Efficient multidisciplinary approach is essential in the management of PA-AML and cardiac disease. Minimally invasive cardiac surgery may be safe and useful in patients with AML.
Keywords: minimally invasive surgery; congenital heart disease; CHD; hematology; pregnancy